Grassroots-Based Waste Management: Implementation of Financial Management - Suryana, Asep; Rifa'i, Asep Achmad; Zaky, Muhammad (PT. Riset Press International, 2025)
The implementation of this Community Service (PKM) activity is a form of attention and participation of academics related to critical issues of waste management with the theme of Grasp-Based Waste Management: Implementation of Financial Management. The goal is an effort to help increase awareness, participation and cooperation in dealing with the waste problem, with theaim of recreating high awareness to participate and cooperate in the implementation method of activities, adapting the observation approach, socialization at the implementation and evaluation stages. Results of the activity. This KKM activity offers three main activities. First, socialization of grassroots-based waste handling; Second, a healthy living culture by paying attention to shopping and consumption behavior; Third, the implementation of Financial Management with economic behavior. The implication is that in the future, similar follow-up activities are needed to support the realization of zero waste and zero residue programs for clean and waste-free living by applying a scientific approach in the implementation of financial management at the individual family level, accompanied by adapting and integrating technology that allows the involvement of various related parties in a continuous manner in waste management among the community.